2023
DOI: 10.1038/s41587-023-01791-y
|View full text |Cite
|
Sign up to set email alerts
|

Strand-selective base editing of human mitochondrial DNA using mitoBEs

Abstract: A number of mitochondrial diseases in humans are caused by point mutations that could be corrected by base editors, but delivery of CRISPR guide RNAs into the mitochondria is difficult. In this study, we present mitochondrial DNA base editors (mitoBEs), which combine a transcription activator-like effector (TALE)-fused nickase and a deaminase for precise base editing in mitochondrial DNA. Combining mitochondria-localized, programmable TALE binding proteins with the nickase MutH or Nt.BspD6I(C) and either the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Our results demonstrated that 11NC (DddA11 + L-1397N + R-1397C) -T1391A-xAID-NES2 variant and WT-DdCBE groups introduced slightly higher bystander edits in the TALE binding sites and sites flanking the binding sites compared to untreated group due to the presence of xAID (Figure S2a, Supporting Information). Moreover, we compared the bystander edits of our high-activity variants with recently published mitoBEs, [33] further confirming the result (Figure S2a, Supporting Information). These results collectively demonstrated that fusion ssDNA cytosine deaminase with DddA in an optimal DdCBE variant (DddA11-T1391A-xAID- The nucleotide adjacent to the end of the left-TALE-recognition sequence was numbered "'1,"' and C was sequentially numbered.…”
Section: Addition Of Ssdna Deaminases In Ddcbe Increased Editing Effi...supporting
confidence: 84%
See 1 more Smart Citation
“…Our results demonstrated that 11NC (DddA11 + L-1397N + R-1397C) -T1391A-xAID-NES2 variant and WT-DdCBE groups introduced slightly higher bystander edits in the TALE binding sites and sites flanking the binding sites compared to untreated group due to the presence of xAID (Figure S2a, Supporting Information). Moreover, we compared the bystander edits of our high-activity variants with recently published mitoBEs, [33] further confirming the result (Figure S2a, Supporting Information). These results collectively demonstrated that fusion ssDNA cytosine deaminase with DddA in an optimal DdCBE variant (DddA11-T1391A-xAID- The nucleotide adjacent to the end of the left-TALE-recognition sequence was numbered "'1,"' and C was sequentially numbered.…”
Section: Addition Of Ssdna Deaminases In Ddcbe Increased Editing Effi...supporting
confidence: 84%
“…Yi et al recently developed the mitoBEs for efficient and accurate mtDNA base editing by combining a ssDNA deaminase and nickase MutH or Nt.BspD6I(C). [33] It is worth mentioning that they expanded the cytosine deaminases beyond DddA for mitochondrial C-to-T base editing. We therefore compared the editing efficiencies of our high-activity variants and the mitoBEs in mtDNA at ND4, ND1, and ND1 (m.G3697) sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, how to accurately edit the target nucleotide and reduce bystander effects is a key factor in deciding its potential applicability. To address this problem, strand-selective ( Yi et al, 2023 ) and strand-preferred DddA variants ( Hu et al, 2023 ) have separately been found one after another, aiming at completing strand-specific mtDNA C>T conversion. In this work, it is found that DdCBE also could enable half-specific or half-prefer C>T conversion in mtDNA editing via proper combinations of DddA halves for aC or tC targets.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that DdCBEs strongly prefer 5′-tC targets or even 5′-aC targets for mtDNA editing ( Boyne et al, 2022 ; Qi et al, 2023 ; Silva-Pinheiro et al, 2023 ), although some labs have expanded the scope of the target by constructing some other DddA variants ( Mok et al, 2022 ; Guo et al, 2023 ; Mi et al, 2023 ; Wei et al, 2023 ). Meanwhile, based on DdCBE, a series of related variants have been developed one after another, including DddAtox mutant-containing DdCBE with higher editing efficiency and broader editing scope ( Mok et al, 2022 ), transcription-activator-like effector-linked deaminases (TALEDs) which can introduce A-G substitution ( Cho et al, 2022 ) and strand-selective base editors (mitoBEs) with high A-G editing efficiency and specificity ( Yi et al, 2023 ), as well as strand-preferred base editor (CyDENT) with high strand-specificity and broader editing scope ( Hu et al, 2023 ). Despite these variants, DdCBE still acts as the most commonly used editor for mtDNA.…”
Section: Introductionmentioning
confidence: 99%
“…with an efficiency of up to 77% and high specificity in human cells while targeting mitochondrial DNA (Yi et al, 2023). It will be interesting to test the nickase in our TALE-ABEs, as this may lead to improved specificity in A•T-to-G•C editing also in the organellar genome of plants.…”
Section: Discussionmentioning
confidence: 99%